Diagnostic Analysis of a Heavy Rainfall in Naqu and Simulation Study of the Source of Water Vapor in the Summer of 2014 - Yuting ZENG; Yu ZHANG; Xizhao WANG; Yitian HAO (Gaoyuan qixiang)
As the "water tower of Asia"， it’s of great significance to study the precipitation sources of the Qinghai-Xizang Plateau for China's water security and water resources utilization.Using the methods of diagnostic analysis and Lagrangian model simulation， a heavy rainfall in Naqu caused by the plateau vortex was analyzed and studied， the source of water vapor in the Naqu area was determined and the contribution of the water vapor source area to the summer precipitation in the study area was further quantified.The results show that there is a strong upward movement over Naqu and has good water vapor conditions.Many strong convective cloud clusters have been formed successively， forming short-term heavy precipitation.The majority of target air blocks that affect precipitation come from the relatively low atmosphere south of the target area and can be traced back to the Bay of Bengal， Arabian Sea and Indian Ocean.In addition， a small part of the target gas block in the western path of the Qinghai-Xizang Plateau comes from the middle and lower atmospheres.High-level water vapor is mainly transported by high-pressure anticyclones in South Asia.A few blocks of gas come from eastern China and the South China Sea.The transportation of water vapor along the western and southern borders is the main source of heavy precipitation in Naqu.The main sources of water vapor are the Indian Ocean， Arabian Sea， India， the Bay of Bengal， Xinjiang， and Central Asia.The water vapor from the Indian Ocean and the Arabian Sea plays a key water vapor contribution to the precipitation area， and the local water vapor contribution is negligible.